Fostering Mathematical Creativity Among Engineering Undergraduates - Keng Keh Lim; Zaleha Ismail; Yudariah Mohammad Yusof (Universitas Diponegoro, 2019)
This research is used to study engineering undergraduates fostering their mathematical creativity during creative problem solving. This was an exploratory research carried out in a public university as to find out the impact of CPS towards mathematical creativity among the engineering undergraduates. A case study was used to provide deep exploration of how the engineering undergraduates using their creative methods to solve open-ended mathematical problems creatively. Qualitative research design was applied in order to understand in depth the engineering undergraduates working collaboratively to generate their creative ideas during mathematical problem solving. Three final years engineering undergraduates took part in the study. They had to use their divergent and convergent thinking to generate creative methods to solve twelve open-ended mathematical problems. Qualitative research design of case study was used in this study to explore the engineering undergraduates using creative methods to solve open-ended mathematical problems during creative problem solving processes. By analyzing the data collected from the case study can provide in-depth and detail understanding of the creative processess and products of the research. Observation and recording sheets were used to collect all the data. SCAMPER was also used as a guideline for them to spark their creaivity. All the qualitative data of drawing from documents, videotape from observation and snapshot texts from recording sheets were collected and then analyzed. They were coded and categorized into different themes in order to find out the mathematical creativity among the engineering undergraduates. The results in this study shows that the engineering undergraduates were able to generate different creative methods with the help of the SCAMPER.